Convenient Synthesis of Spiro[benzo[d]pyrrolo[2, 1‐b]thiazole‐3, 2′‐indenes] Derivatives via Three‐Component Reaction. Issue 4 (14th March 2016) - Shen, Guoliang; Sun, Jing; Yan, Chaoguo
Abstract: The three‐component reaction of N ‐phenacylbenzothiazolium bromides, aromatic aldehydes and indane‐1, 3‐dione in ethanol at room temperature in the presence of triethylamine as base afforded functionalized spiro[benzo[ d ]pyrrolo[2, 1‐ b ]thiazole‐3, 2′‐indenes] in good yields and with high diastereoselectivity. The 1 H NMR data and single crystal structure clearly indicated that the obtained spiro compounds predominately have one diastereoisomer. Abstract : The three‐component reactions of N ‐phenacylbenzothiazolium bromides, aromatic aldehydes and indane‐1, 3‐dione afforded functionalized spiro[benzo[ d ]pyrrolo[2, 1‐ b ]‐thiazole‐3, 2′‐indenes] in good yields and with high diastereoselectivity.